The Copyright Wars : Three Centuries of Trans-Atlantic Battle. - Baldwin, Peter, 1956- (Princeton University Press, 2014)
Today's copyright wars can seem unprecedented. Sparked by the digital revolution that has made copyright -- and its violation -- a part of everyday life, fights over intellectual property have pitted creators, Hollywood, and governments against consumers, pirates, Silicon Valley, and open-access advocates. But while the digital generation can be forgiven for thinking the dispute between, for example, the publishing industry and Google is completely new, the copyright wars in fact stretch back three centuries -- and their history is essential to understanding today's battles. Peter Baldwin explains why the copyright wars have always been driven by a fundamental tension. Should copyright assure authors and rights holders lasting claims, much like conventional property rights, as in Continental Europe? Or should copyright be primarily concerned with giving consumers cheap and easy access to a shared culture, as in Britain and America? This book describes how the Continental approach triumphed, dramatically increasing the claims of rights holders. It also tells the widely forgotten story of how America went from being a leading copyright opponent and pirate in the eighteenth and nineteenth centuries to become the world's intellectual property policeman in the late twentieth.